2013
DOI: 10.7575/aiac.ijalel.v.3n.1p.187
|View full text |Cite
|
Sign up to set email alerts
|

Prepositions and ESL Learners: the Malaysian Scenario

Abstract: This article presents a review of the literature on prepositions with a focus on definitions and main difficulties faced by Malaysian students. It further highlights recommendations about the role of syllabus designers, textbook writers and teachers in meeting these challenges. It is hoped that this article could provide a platform for any further studies on prepositions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The errors highlighted above may not be unique only to Tamil school students but also to other learners of English. They also make errors in their usage of singular and plural forms and prepositions (Darus & Subramaniam, 2009) and in the use of prepositions after verbs, adjectives or nouns in expressions (Roslim, 2013). If a second language learner faces difficulties in learning the English language, the state of affairs in Tamil schools could be even worse, since the students need to master three languages at the same time.…”
Section: Tamil Interference In English Writingmentioning
confidence: 99%
“…The errors highlighted above may not be unique only to Tamil school students but also to other learners of English. They also make errors in their usage of singular and plural forms and prepositions (Darus & Subramaniam, 2009) and in the use of prepositions after verbs, adjectives or nouns in expressions (Roslim, 2013). If a second language learner faces difficulties in learning the English language, the state of affairs in Tamil schools could be even worse, since the students need to master three languages at the same time.…”
Section: Tamil Interference In English Writingmentioning
confidence: 99%
“…Writing errors are some grammatically inappropriate errors. As mentioned by Roslim & Mukundan (2014), grammar has constantly been examined as an indispensable content in teaching English, especially EFL and ESL. Learning grammar is a difficult thing for students, since there are several edicts that cannot be disregarded, and the usual faults frequently detected in learners' writing are preposition errors.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to do so will result in learners facing problems in communication. If this problem is not tackled from the early school years, it will eventually affect the learners' communicative ability at tertiary level and later on in life (Roslim & Mukundan, 2014). Results from studies such as Ahour and Mukundan (2012), Hong et al (2011), Kamariah and Su'ad (2011), Ting et al (2010), andSudhakaran (2008) have shown that students at tertiary level in universities in Malaysia still encounter problems with prepositions.…”
Section: Introductionmentioning
confidence: 99%